Pengaruh Penggunaan Starter Bakteri Asam Laktat Lactobacillus plantarum dan Lactobacillus fermentum terhadapTotal Bakteri Asam Laktat, Kadar Asam dan Nilai pH Dadih Susu Sapi - Afriani, Afriani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The  objective  of  the  current  study    to  determine  the  effect  of  the  use  of  bacteria  Lactobacillus plantarum and Lactobacillus fermentum in the manucfacture of cow’s milk curd on the total lactid acid bacteria, acidity and pH value of cow’s milk curd. The experiment use fresh cow milk and starter culture of Lactobacillus plantarum, and L. plantarum. Starter culture added about 3% from milk volume than incubated at  room  temperature during 48 hours. The treatments were  fermentation with L. plantarum (A1); L. fermentum (A2); L. plantarum + L. fermentum  (A3). There were significant effect of addition of starter L. plantarum (A1), L. fermentum (A2), and the combination of L. plantarum + L. fermentum (A3) on total  lactic acid bacteria and acidity, however, there was no statistically significant on the pH value of cow's milk curd. It was concluded that using of starter culture combinations of Lactobacillus plantarum  +  Lactobacillus  fermentum  (A3)  increases  the  total  lactic  acid  bacteria  and  acid  levels  of cow’s milk curd.